Internal Occipital Crest Misalignment with Internal Occipital Protuberance: A Case Report of Posterior Cranial Fossa Anatomic Variations - Jae Ha Kim; Maha Ahmad (Case Reports in Neurological Medicine)
During gross anatomy head and neck laboratory session, one dissection group observed an abnormal anatomic variation in the posterior cranial fossa of a 94-year-old male cadaver. The internal occipital crest was not aligned with internal occipital protuberance and groove for superior sagittal sinus. It seemed that the internal occipital protuberance was shifted significantly to the right side. As a result the skull was overly stretched in order to connect with the internal occipital ridge. These internal skull variations of occipital bone landmarks can influence the location of adjacent dural venous sinuses and possibly influence cerebrospinal fluid flow. Similar anatomical anomalies have been attributed to presence of hydrocephalus and abnormalities in cisterna magna.